2018
DOI: 10.1016/j.ijscr.2017.12.033
|View full text |Cite
|
Sign up to set email alerts
|

Ileal GIST presenting with bacteremia and liver abscess: A case report and review of literature

Abstract: HighlightsSmall intestine gastrointestinal stromal tumors can infrequently present with intra-abdominal abscess, perforation, obstruction or fistula.Tumor-small intestine fistula is a rare phenomenon and occurs as a result of GISTs’ propensity to cause mucosal ulceration.Although liver metastases are common, in the rare case of a GIST complicated by gastrointestinal tract perforation, abscess or fistula, a pyogenic liver abscess is another important entity to consider.Positive blood cultures with members of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 18 publications
0
6
1
Order By: Relevance
“…2 Although there have been isolated case reports of GISTs presenting with enterocolic or vesicocutaneous fistulas, these patients often presented with overt clinical signs or symptoms as mentioned. 4 By contrast, our patient's fistula was found incidentally during workup for an unrelated anemia. Radiographic evidence of fistulization may include the presence of air fluid levels within the suspected mass.…”
Section: Discussioncontrasting
confidence: 57%
“…2 Although there have been isolated case reports of GISTs presenting with enterocolic or vesicocutaneous fistulas, these patients often presented with overt clinical signs or symptoms as mentioned. 4 By contrast, our patient's fistula was found incidentally during workup for an unrelated anemia. Radiographic evidence of fistulization may include the presence of air fluid levels within the suspected mass.…”
Section: Discussioncontrasting
confidence: 57%
“…A review of the literature has demonstrated that primary liver abscesses when associated with primary GIST are often caused by commensal, obligate, or facultative anaerobic organisms [ 17 ]. Alpha hemolytic streptococcus infections, which are part of the mucosal flora of the GI tract, such as Streptococcus milleri and Streptococcus intermedius, have been implicated [ 17 , 18 ]. While there are limited data on liver abscesses and primary GIST, common causes of pyogenic liver abscesses are related to hepatic malignancy, biliary tract disease, and gut microbiota dysbiosis [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Emerging studies have also noted a relationship between gut microbiota dysbiosis and the development of GIST, which we would recommend further exploration [ 19 ]. Nonetheless, if there is a concern for liver metastasis, it is recommended that patients undergo diagnostic workup for pyogenic liver abscesses as well, so they are promptly initiated on appropriate antibiotics [ 18 ]. Conversely, the identification of an alpha-hemolytic streptococcus infection or, generally, an anaerobic infection should prompt further evaluation of GI tract malignancies [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Gorelik et al [7] reported another rare presentation of GIST. The patient presented in bacteraemia with liver abscess.…”
Section: Discussionmentioning
confidence: 99%